2019
DOI: 10.3847/1538-3881/ab2cd6
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter’s Atmospheric Variability from Long-term Ground-based Observations at 5 μm

Abstract: Jupiter's banded structure undergoes strong temporal variations, changing the visible and infrared appearance of the belts and zones in a complex and turbulent way due to physical processes that are not yet understood. In this study we use ground-based 5-µm infrared data captured between 1984 and 2018 by 8 different instruments mounted on the Infrared Telescope Facility in Hawai'i and on the Very Large Telescope in Chile to analyze and characterize the long-term variability of Jupiter's cloud-forming region at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 73 publications
(150 reference statements)
1
31
0
Order By: Relevance
“…1 are most likely related to changes in the altitude, thickness, and optical properties of the aerosols in (i) the condensate clouds formed from key volatiles (NH 3 , H 2 S, and H 2 O, in addition CH 4 on the cold ice giants) and (ii) photochemically-produced hazes from tropospheric (e.g., PH 3 , NH 3 ) and stratospheric (hydrocarbons like ethane and acetylene) chemistry. On Jupiter there is a close correspondence between red-brown visible colours in the belts and an absence of clouds sensed in the 1-4 bar range (sensed at 5 µm, Ingersoll et al 2004;Fletcher et al 2017c;Antuñano et al 2019), as well as an absence of upper-tropospheric aerosols near 500 mbar (sensed at 8-9 µm, . Conversely, Jupiter's visibly-white zones appear dark at thermal infrared wavelengths, suggesting thick and high clouds over these zones.…”
Section: Clouds and Hazesmentioning
confidence: 72%
See 1 more Smart Citation
“…1 are most likely related to changes in the altitude, thickness, and optical properties of the aerosols in (i) the condensate clouds formed from key volatiles (NH 3 , H 2 S, and H 2 O, in addition CH 4 on the cold ice giants) and (ii) photochemically-produced hazes from tropospheric (e.g., PH 3 , NH 3 ) and stratospheric (hydrocarbons like ethane and acetylene) chemistry. On Jupiter there is a close correspondence between red-brown visible colours in the belts and an absence of clouds sensed in the 1-4 bar range (sensed at 5 µm, Ingersoll et al 2004;Fletcher et al 2017c;Antuñano et al 2019), as well as an absence of upper-tropospheric aerosols near 500 mbar (sensed at 8-9 µm, . Conversely, Jupiter's visibly-white zones appear dark at thermal infrared wavelengths, suggesting thick and high clouds over these zones.…”
Section: Clouds and Hazesmentioning
confidence: 72%
“…Future missions to the ice giants must find a way to probe the circulation patterns below the top-most clouds of methane and H 2 S ice (e.g., . And continued monitoring of temporal variations and episodic outbursts in the belts and zones (Sanchez-Lavega et al 2018;Fletcher 2017;Antuñano et al 2018Antuñano et al , 2019 could reveal insights into the shifting balance between the meridional circulation cells, and the forces determining their quasi-periodic timescales.…”
Section: Discussionmentioning
confidence: 99%
“…and Antuñano et al (2019). At 5 μm, images from late 2018 showed that, for the first time in 13 years, the EZ started to display bright patches at 2-5 • S. However, 5-μm images from mid-2019 showed that the unfolding disturbance was not behaving like previous ones, with only some regions of the EZ becoming bright at 5 μm as if the disturbance stopped half way through, making this disturbance quite unique (see Figure 8 and Figure 8 in Wong et al, 2020).…”
Section: 1029/2020je006413mentioning
confidence: 99%
“…Studies of the long‐term variability of Jupiter's EZ at 5 μm (Antuñano et al, 2018, 2019) have revealed that the EZ displays a quasi‐periodic planetary‐scale disturbance that completely changes its appearance at infrared and visible wavelengths every 7 years (Antuñano et al, 2019). During the disturbed periods, the usually cloudy and 5‐μm‐dark EZ appears highly unusual: (i) a narrow 5‐μm‐bright band develops between 2°S and 5°S, and (ii) a rare wave‐like pattern with 5‐μm‐bright narrow filaments (festoons) becomes visible, connecting the NEB and the newly brightened band south of the equator.…”
Section: Introductionmentioning
confidence: 99%
“…High clouds of icy NH 3 or storm-driven H 2 O clouds obscure deeper atmospheric levels (e.g., see Figure 1). And recent observations suggest an atmosphere as variable and tumultuous as the swirling clouds suggest (e.g., Antuñano et al, 2019;Bolton et al, 2017;de Pater et al, 2016;Fletcher, 2017Li et al, 2017). Although the Galileo Probe provided crucial measurements of Jupiter's troposphere, it descended into an anomalously dry "hot spot" region (features found along the boundary between the equatorial zone and the north equatorial belt) characterized by low cloud opacity, low abundances of cloud-forming species, high thermal (5-μm) emission, and a water abundance that was still increasing with depth when the probe signal was lost at the 22-bar level (e.g., Niemann et al, 1998;Orton et al, 1998;Wong et al, 2004).…”
Section: Prelude To Junomentioning
confidence: 95%